Pengaruh Penetrasi, Densitas Asuransi Non Jiwa dan Non-Performing Loan Perbankan terhadap Pertumbuhan Perekonomian Indonesia - Deviar, Alfiansyah; Djuminah, Djuminah (Universitas Pamulang, 2024)
Referring to Swiss-RE data for 2020-2021, from the percentage of Non-Life Insurance Penetration and Density, the value of Non-Life Insurance Penetration and Density in Indonesia is still relatively small. This study focuses on the effect of Non-Life Insurance Penetration and Density variables on Non-Performing Loans (NPL) and GDP Growth. The scope of research is on OECD countries and Indonesia, which represent developing countries using the Granger Causality Cause method. The results show that in countries with good economic levels, such as OECD countries, Non-Life Insurance Penetration and Density do not occur two-way causality on Non-Performing Loan and GDP Growth. However, a two-way causality relationship occurs in Indonesia due to geological factors and people's risk behaviour.